Nutrition Education Intervention with the Peer Educator Method in Efforts to Overcome Overnutrition in Adolescents - K., Iriyani; Wirapuspita Wisnuwardani, Ratih; Suryaningsi, Suryaningsi (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Overnutrition is one of the health problems that still has a high prevalence in East Kalimantan. Adolescence is a period that is vulnerable to nutritional problems because it is still in the process of growth and development that requires nutritional intake according to needs, nutritious and balanced. Objective : This study aims to improve adolescent knowledge through the peer educator method at SMP Negeri 2 Samarinda. Research Methods/ Implementation Methods : The method used is cross-sectional with a sample of 53 students. The instrument used is a questionnaire given as a pre-test and post-test before and after being given nutrition education consisting of 20 knowledge questions, 15 attitude questions, and 13 practice questions about balanced nutrition, related to balanced nutrition material. To see the difference in knowledge, attitude, and practice values before and after being given nutrition education using the Paired Sample T-Test. The results showed that there was a significant difference (p = 0.001) in the values of knowledge, attitude, and practice before and after being given balanced nutrition education. Results : The results showed an average increase in knowledge of 22.36 ± 14.19, attitudes of 18.51 ± 9.26, and practices of 20.81 ± 12.70. Conclusion/Lesson Learned : This shows that nutrition education training with the peer educator method is effective in improving students' knowledge, attitudes, and practices at SMP Negeri 2 Samarinda.